Configuration effects of enterprise digitization and innovation capability of strategic emerging industries - Zhao-Conghui; Fan-Hejun (Scientific Reports)
Abstract The development of strategic emerging industries is a necessary condition to achieve industrial transformation and upgrading. And industrial digitalization has given strategic emerging industries a new opportunity to accelerate their development. The aim is to explore the configuration effects of digital transformation and innovation capabilities in strategic emerging industries. This paper using the fuzzy-set qualitative comparative analysis. Seven representative condition variables are selected for configuration analysis from three dimensions: digital transformation awareness, digital transformation capability and digital transformation achievement to conduct configuration analysis. The results show that: (1) There are three configurations to improve the innovation capability of strategic emerging industries, which are digital awareness leads, digital capability facilitation and digital innovation breaks through substitution. (2) The configuration effect of digital transformation on innovation capability of strategic emerging industries in different regions of China is different. To enhance the innovation ability of strategic emerging industries, we should attach importance to the core role of digital innovation awareness.